Practical aspects in electrolyte management in PICU - Kundan Mittal; H K Aggarwal; Sachin Damke; Jayant Wagha (Wolters Kluwer Medknow Publications, 2019)
Fluid and electrolytes management is key to pediatric critical care. These disorders may be primary or secondary to illness, drugs, iatrogenic, or as a result of medical error. The electrolyte disturbances are seen frequently and require aggressive monitoring and management. It is essential to understand normal water and electrolyte physiology and their distribution in human body for the management.